Flight control systems practical issues in design and implementation - Pratt, Roger, 1943- (Institution of Electrical Engineers ; American Institute of Aeronautics and Astronautics, 2000)
Annotation Bridging the gap between academic research and real-world applications, this reference on modern flight control methods for fixed-wing aircraft deals with fundamentals of flight control systems design, then concentrates on applications based on the modern control methods used in the latest aircraft. The book is written for practicing engineers who are new to the aviation industry, postgraduate students in strategic or applied research, and advanced undergraduates. Some knowledge of classical control is assumed. Pratt is a member of IEEE and is UK Member for AIAA's Technical Committee on Guidance, Navigation and Control. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Keywords: Airplanes -- Control systems -- Design and construction.; Flight control.; elektronické knihy; electronic books